Analisis Dampak Pinjaman Modal Usaha Terhadap Pendapatan dan Laba Pedagang di Pasar Batuah Martapura - Zulkifli; Nasrudin (PPJP ULM, 2019)
This study is done to know how the traders are felt after receiving credit venturecapital loans and the extent of income and profits development of merchants at the market oftaibah Martapura after receiving investment capital loans from banks and from markets.The method used in this study is to describe comparative descriptive and approach. Thepopulation in this study was that of merchants who used their own capital and who usedventure capital from both banks and markets, as many as 30 people. The methods of sampletaking use of purposive side methods. The number of samples in the study of 30 people, thedata is processed using Mann Whitney's U-Test test to see the comparison between the owncapital and the borrowed capital.Studies show that differences in the income and profits levels of the traders undergosignificant changes in self-use and after receiving business capital loans. Test resultsconducted with the Mann-Whitney u-test method using the SPSS indicate the output of thestatistical test, that the value of A sig. (2-tailed) in the amount of 0.001, 0.000, 0.005, and0.002 smaller than 0.05. Then it could be concluded that hypotheses are this accepted thatthere is a difference I income and profit between their own capital and borrowed capital.The biggest problem for business traders is their limited ability to invest.